Gasoline and diesel demand in Europe: New insights - Markus Pock (Institute for Advanced Studies (IHS), 2007)
This study utilizes a panel data set from 14 European countries over the period 1990-2004 to estimate a dynamic model specification for gasoline and diesel demand. Previous studies estimating gasoline consumption per total passenger cars ignore the recent increase in the number of diesel cars in most European countries leading to biased elasticity estimates. We apply several common dynamic panel estimators to our small sample. Results show that specifications neglecting the share of diesel cars overestimate short-run income, price and car ownership elasticities. It appears that the results of standard pooled estimators are more reliable than common IV/GMM estimators applied to our small data set.
Keywords: C23; Q41; 330; dynamic panel data; gasoline demand; error components; omitted variable; Benzin; Dieselkraftstoff; Energiekonsum; Gesamtwirtschaftliche Nachfrage; Schätzung; Europa